2015
DOI: 10.1007/s40846-015-0060-5
|View full text |Cite
|
Sign up to set email alerts
|

Review: Application of Nanoparticles in Urothelial Cancer of the Urinary Bladder

Abstract: Bladder cancer is a common malignancy of the urinary tract, which generally develops in the epithelial lining of the urinary bladder. The specific course of treatment depends on the stage of bladder cancer; however, therapeutic strategies typically involve intravesical drug delivery to reduce toxicity and increase therapeutic effects. Recently, metallic, polymeric, lipid, and protein nanoparticles have been introduced to aid in the treatment of bladder cancer. Nanoparticles are also commonly used as pharmaceut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 119 publications
0
17
0
Order By: Relevance
“…Similarly, Chen et al used a gold nanoplatform attached to mucin seven antibodies with the capability of PTT in urothelial cancer cell lines. They showed that immunized gold nanospheres significantly reduced the energy level required to kill cancer cells using PTT when compared with nontargeted cancer cells …”
Section: Nps For Targeted Cancer Therapymentioning
confidence: 99%
“…Similarly, Chen et al used a gold nanoplatform attached to mucin seven antibodies with the capability of PTT in urothelial cancer cell lines. They showed that immunized gold nanospheres significantly reduced the energy level required to kill cancer cells using PTT when compared with nontargeted cancer cells …”
Section: Nps For Targeted Cancer Therapymentioning
confidence: 99%
“…Compatibility of gold with biosystems has been well demonstrated since metallic nanoscale materials were originally developed [33]. In recent years, synthesis and application of gold NPs (AuNPs) in the biomedical field have substantially increased due to their ductility physicochemical properties and biocompatibility.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…The synergistic effect of AuNPs and laser-induced thermotherapy renders thermally exposed cancer cells susceptible to be ablated with minimal exposure times and lower laser intensities [33]. Rau, et al showed that AuNPs could cause severe damage in the cytoskeleton of MG63 osteosarcoma cells in combination with laser treatment, increasing the calcium content inside the cells and leading to mineralization [41].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…But permeability through bladder is difficult to achieve. In this case, nanoparticles could be the choice as it has the ability to penetrate the barrier more easily because of its nanosized component [23]. The unique advantage of the nanoparticle is that it can target cancer cells either in the active or passive way and it can be given locally in tumor sites which help to reduce the shortcomings of conventional chemotherapy [24].…”
Section: Nanoceria In Cancer Therapymentioning
confidence: 99%